JUVENILE ARTHRITIS: DIAGNOSTICS AND TREATMENT - Людмила Николаевна Игишева; Светлана Сергеевна Притчина; Юлия Александровна Быкова; Александра Александровна Аникеенко (Мать и дитя в Кузбассе, 2017)
There are some theoretical and practical issues which are connected with different aspects of arthritis in children are discussed in the guideline. Such aspects are appealed to systematize and optimize the diagnostic process and this is very important, because children with early signs of the disease are usually resorted to the pediatricians. This guideline describes modern technologies of the juvenile arthritis treatment – a chronic disease with distinct tendency to the children disablement and involvement of internal organs as well as eyes to the pathological process. Only modern diagnostics and adequate treatment can prevent or lessen hard sequelae of this social disease. The guideline is intended for the pediatricians, rheumatologists, children surgeons, as well as for medical residents and postgrads.